A7RC peptide modified paclitaxel liposomes dually target breast cancer. (20th August 2015) - Cao, Jingyan; Wang, Ran; Gao, Ning; Li, Minghui; Tian, Xuyu; Yang, Weili; Ruan, Ying; Zhou, Chunlan; Wang, Guangtian; Liu, Xiaoying; Tang, Shukun; Yu, Yan; et al.
Abstract : A7RC enhanced the accumulation of paclitaxel liposomes in a neuropilin-1 high expressing breast cancer mouse model and inhibited tumor growth and angiogenesis. Abstract : A7R peptide (ATWLPPR), a ligand of the NRP-1 receptor, regulates the intracellular signal transduction related to tumor vascularization and tumor growth. Here, we designed A7R-cysteine peptide (A7RC) surface modified paclitaxel liposomes (A7RC-LIPs) to achieve targeting delivery and inhibition of tumor growth and angiogenesis simultaneously. The cytotoxicity, inhibiting angiogenesis, and internalization of various liposomes by cells were assessed in vitro to confirm the influence of the peptide modification. The accumulations of A7RC-LIPs in various xenografts in mice were tracked to further identify the function of the peptide on the liposomes' surface. The results confirmed that A7RC peptides could enhance the uptake of vesicles by MDA-MB-231 cells, leading to stronger cytotoxicity in vitro and higher accumulation of vesicles in MDA-MB-231 xenografts in vivo . In addition, A7RC peptides enhanced the inhibitory effects of LIPs on the HUVEC tubular formation on Matrigel. The A7RC-LIPs may be promising drug carriers for anticancer therapy.